Ugly animals - Marsh, Laura F.; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2015)
Learn about ugly animals and how their strange bodies help protect them.
These animals may not be pretty, but they're all around us! Marsh introduces readers to some "ugly" animals and explains how what looks strange to us actually helps them survive.
What is that? -- On the ground -- Under the earth -- In the air -- Fabulous frogs -- In the water -- In the trees -- In outer space?! -- Quiz whiz.
OSLIS\Gale Nat Geo eBooks(2/2/23).
"Be a Nat Geo Kids super reader"--Cover.
Ages 5-8.
Description based on print version record.
Keywords: Animals -- Miscellanea -- Juvenile literature; Animals; Animals -- Miscellanea; JUVENILE NONFICTION / Animals; JUVENILE NONFICTION / Reader - Intermediate; Electronic books- OSLIS; Juvenile works; Miscellanea; Children's nonfiction; Children's readers; Electronic books